The Journey of Herpes Zoster from Myths towards Facts......!! - Sagar Goyal; Akshay Salgar; Gayatri G. Dhavalshankh; Sheetal .; Ganesh P. Dhavalshankh; Archana G. Dhavalshankh (Recent Updates in Disease and Health Research Vol. 7, 2024)
Background: Herpes zoster (HZ) is an acute highly contagious infection caused by the varicella-zoster virus (VZV). In India, there is a paucity of population-based studies and data on herpes zoster in reporting herpes zoster cases. Several shreds of evidence reflect that the disease causes a burden on population health in India. Besides several known risk factors, myths, lack of knowledge, attitude, and practices towards treating this infection may affect the quality of life and disease burden. Imparting knowledge, awareness regarding myths and misconceptions, and early approaches for treatment can help prevent disease and complications in the population. The study aims to evaluate the impact of herpes zoster infection awareness programs on myths, knowledge, and practices among the rural population. Methods: This study is an interventional study that was conducted over 4 months (July to October 2023) in the rural population of western Maharashtra and Families of adopted villages by D.Y. Patil Medical College, Kolhapur from the rural field practice area of the medical college. Our study variables were myths about herpes zoster infection, knowledge about herpes zoster infection, and attitudes and practices towards the treatment of herpes zoster infection to evaluate the impact of the health awareness program on it. Results: The awareness program which was the intervention in this study, was effective in increasing the awareness about myths and knowledge about herpes zoster infection as well as the positive impact related to treatment practices for herpes zoster infection among the rural population in the adapted villages in western Maharashtra. For example, this study showed an improvement in the knowledge of the participants after implementing an awareness program. This study showed that after the awareness program, 91.30% of people learned it is a viral disease, and 85.34% learned that it is not a superstitious thing. Conclusions: The awareness program which was the intervention in this study, was effective in increasing the awareness about myths and knowledge about herpes zoster infection as well as positive impact related to treatment practices for herpes zoster infection among the rural population in the adapted villages in western Maharashtra. To change the attitude and clear the myths need more effort and faith with more conversation, more visits, interactive sessions, more trained, competent, and confident students, volunteers, and community support for a better and more effective impact of this awareness program.